Seeking Resistance in Coral Reef Ecosystems: The Interplay of Biophysical Factors and Bleaching Resistance under a Changing Climate: The Interplay of a Reef's Biophysical Factors Can Mitigate the Coral Bleaching Response. (19th June 2019) - Page, Charlotte E.; Leggat, William; Heron, Scott F.; Choukroun, Severine M.; Lloyd, Jon; Ainsworth, Tracy D.
Abstract : If we are to ensure the persistence of species in an increasingly warm world, of interest is the identification of drivers that affect the ability of an organism to resist thermal stress. Underpinning any organism's capacity for resistance is a complex interplay between biological and physical factors occurring over multiple scales. Tropical coral reefs are a unique system, in that their function is dependent upon the maintenance of a coral–algal symbiosis that is directly disrupted by increases in water temperature. A number of physical factors have been identified as affecting the biological responses of the coral organism under broadscale thermal anomalies. One such factor is water flow, which is capable of modulating both organismal metabolic functioning and thermal environments. Understanding the physiological and hydrodynamic drivers of organism response to thermal stress improves predictive capabilities and informs targeted management responses, thereby increasing the resilience of reefs into the future. Abstract : Driving patterns of coral bleaching over reefs are a suite of biophysical interactions where the physical environment modulates organism response through an interplay with intrinsic biological functioning. Flow conditions over reefs can mitigate the physiological impacts of thermal stress across multiple spatial scales.